C-MET as a potential target therapy toward personalized therapy in some pediatric tumors: An overview. (November 2018) - Rashed, Wafaa M.
Abstract: Althoughpediatric tumors represent less than 1% of all new cancer diagnoses, they still rank the second in the list of disease-related morbidity and mortality in children in the US. Combining biomarker-driven targeted therapy with individualized genomic analysis is the principle of precision medicine trials. The cellular–mesenchymal-epithelial transition (c-MET) factor receptor signaling pathway plays an important role in many physiological functions including embryological development. It, tightly, regulates changes in cell growth and survival, it also defines the general pattern of invasive growth during normal development. Aberrant MET signaling is the fundamental cause of carcinogenesis of many pediatric tumors and it may play a role in tumor metastasis that leads to the poor prognosis in most cancer patients. This review describes c-MET/hepatocyte growth factor (HGF) signaling pathway relevance to pediatric tumors. Also, it discusses the pre-clinical and clinical studies for inhibitors of this pathway.